Replication of linear plasmids in bacteria - Chaconas, George (Henry Stewart Talks, 2008)
The end replication problem and solutions, Replication of linear DNA in Streptomyces species using terminal proteins, Replication of linear DNA in Borrelia species using telomere resolution, Genome plasticity in Borrelia resulting from reversal of telomere resolution
Archived at 2024/01/31